PENGARUH FAKTOR KEPERILAKUAN ORGANISASI TERHADAP IMPLEMENTASI SISTEM AKUNTANSI KEUANGAN DAERAH DALAM MEWUJUDKAN TRANSPARANSI DAN AKUNTABILITAS KEUANGAN - Arthur Simanjuntak (JURNAL MANAJEMEN, 2017)
The purpose of this study is to determine and analyze the effect of organizational behavior factors on the implementation of financial accounting system use area in realizing financial transparency and accountability. This research uses descriptive analysis techniques and multiple linear regression analysis and path analysis test. The results of the study show that there is an influence of organizational behavior factors (support superior, goal clarity, training and organizational commitment) on financial transparency and accountability. There is an influence of behavioral factors (support superior, goal clarity and training) on transparency and accountability through the implementation of financial accounting system use area. While organizational behavior factors (organizational commitment) directly influence transparency and accountability of regional finances.